2011
DOI: 10.1007/s10964-011-9703-1
|View full text |Cite
|
Sign up to set email alerts
|

Marital Conflict and Early Adolescents’ Self-Evaluation: The Role of Parenting Quality and Early Adolescents’ Appraisals

Abstract: Cognitive appraisals and family dynamics have been identified as mediators of the relationship between marital conflict and children's adjustment. Surprisingly little research has investigated both meditational processes in the same study. Guided by the cognitive-contextual framework and the spillover hypothesis, the present study integrated factors from both theories early adolescents' appraisals of threat and self-blame, as well as perceived parenting quality as mediators of the link between early adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 50 publications
2
19
0
4
Order By: Relevance
“…Three mechanisms that account for the potential impact of family confl ict on adolescent adjustment have been empirically evaluated. Focusing mostly on interparental confl ict and adolescent self-esteem (a signifi cant predictor of mental health outcomes), these mechanisms highlight the importance of adolescents' cognitive appraisal of the meaning of interparental confl ict (e.g., "I am responsible for problems in my family") (Grych, 1998;Shelton and Harold, 2008) and "spillover" of interparental confl ict into parenting quality (where resources for effective parenting are depleted by interparental confl ict; Erel and Burman, 1995;Siffert et al, 2012). Other research suggests that girls are more vulnerable to family stress than boys, that family stress is more predictive of depressed mood for girls than boys, and that girls may be more likely to engage in avoidant coping than boys (Kort-Butler, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Three mechanisms that account for the potential impact of family confl ict on adolescent adjustment have been empirically evaluated. Focusing mostly on interparental confl ict and adolescent self-esteem (a signifi cant predictor of mental health outcomes), these mechanisms highlight the importance of adolescents' cognitive appraisal of the meaning of interparental confl ict (e.g., "I am responsible for problems in my family") (Grych, 1998;Shelton and Harold, 2008) and "spillover" of interparental confl ict into parenting quality (where resources for effective parenting are depleted by interparental confl ict; Erel and Burman, 1995;Siffert et al, 2012). Other research suggests that girls are more vulnerable to family stress than boys, that family stress is more predictive of depressed mood for girls than boys, and that girls may be more likely to engage in avoidant coping than boys (Kort-Butler, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Dichos hallazgos son coherentes con los presentados por otros estudios que muestran que la percepción de aceptación, calidez o afecto en la relación con los padres se vinculan con autopercepciones más positivas. Por el contrario, las formas negativas de control (el control psicológico, la coerción y la intrusividad) se asocian a autopercepciones más negativas (Frank et al, 2010;Reina et al, 2010;Siffert et al, 2012).…”
Section: Discusión Y Conclusionesunclassified
“…el control psicológico, la coerción, el caos) se asocian con autopercepciones más negativas (e.g. Clerici & García, 2011;Frank, Plunkett, & Otten, 2010;Fuentes, García, Gracia, & Alarcón, 2014;Reina, Oliva Delgado, & Parra Jiménez, 2010;Richaud de Minzi, 2006a;Siffert, Schwarz, & Stutz, 2012).…”
unclassified
“…In addition, while higher perceived teacher support and school belonging related to less school misconduct, higher peer attachment associated with higher rates of school misconduct. Siffert et al (2012), in a study of 176 two-parent families longitudinally examined early adolescents' appraisals of threat and self-blame, as well as perceived parenting quality, as mediators of the link between early adolescents' perception of marital conflict and their self-evaluations (self-esteem and scholastic competence). Their analyses indicated that parenting quality and early adolescents' perceived threat provided indirect pathways between marital conflict and early adolescents' self-esteem 1 year later when controlling for their initial level of self-esteem.…”
mentioning
confidence: 99%